Meyer Schapiro’s method: art criticism through style and context - Zulkiflli, Siti Ayisah; Mohd Din, Nurul Huda; Tohid, Mohd Suhaimi (Faculty of Art and Design, 2025)
This paper resurrects the revolutionary spirit of Meyer Schapiro, the maverick art historian who dared to see canvases as battlefields of ideology. Rejecting the stale dogma of “art for art’s sake,” Schapiro weaponized formal analysis to expose how every brushstroke whispers secrets about power, rebellion, and cultural DNA. In incendiary texts like Style (Schapiro,1953) and The Nature of Abstract (Schapiro,1937), he shattered the ivory tower of pure aesthetics, proving that a Baroque flourish or Cubist fracture isn’t just technique—it’s a time capsule of class struggle, philosophical wars, and the tectonic shifts of history. Through a Molotov cocktail of sociology, Marxist theory, and razor-sharp visual analysis, Schapiro rewired art history into a detective game where style betrays its maker’s world. This paper dissects how his insurgent methodology—part cultural archaeology, part political manifesto—continues to electrify contemporary art criticism, equipping us to decode the hidden rebellions and silent screams embedded in form itself. Schapiro’s legacy? A radical lens that transforms galleries into crime scenes, demanding we interrogate not just what art shows, but what it betrays.